Hypoparathyroidism, an innate risk of thyroidectomy - S., Arun; Ravindran, Rashmi; P., Sreejayan M. (International Surgery Journal, 2017)
Background: The identification and preservation of parathyroid glands (PT) with its intact blood supply is of utmost importance during thyroid surgery. To preserve the PT with intact blood supply, a medial to lateral dissection is advocated, with plane of dissection along the thyroid capsule. One of the earliest and feared complications of thyroidectomy is hypoparathyroidism (HPT). Aim was to study the incidence of temporary and permanent hypoparathyroidism during thyroidectomy. Methods: This was a hospital based prospective study, from 2008 to 2015. 472 cases who underwent thyroidectomy (182 near total and 290 total thyroidectomies) for any indications in general surgery department of a tertiary care centre were included. Results: The incidence of permanent and transient HPT after total thyroidectomy was 3.8 and 09%, where as it was 2.75 and 3.85% after near total thyroidectomy. The results of present study were comparable with other studies. Conclusions: Meticulous dissection, absolute hemostasis, and a thorough knowledge of neck anatomy are the key in reducing the post thyroidectomy complications. Transient or permanent hypo parathyroidism is due to inadvertent gland removal or injury to its vascular pedicle. Dissection close to the thyroid capsule and ligation of capsular branches of thyroid avoiding the main trunk of inferior thyroid artery holds the key.